Voting when the stakes are high - Jørgen Juel Andersen; Jon H. Fiva; Gisle James Natvik (Center for Economic Studies and ifo Institute (CESifo), 2010)
Rational choice theories of electoral participation stress that an individual's decision to vote depends on her expected net benefit from doing so. If this instrumental motive is relevant, then turnout should be higher in elections where more is at stake. We test this prediction, by studying how turnout is affected by exogenous variation in governments' financial flexibility to provide pork for their voters. By utilizing simultaneous elections for different offices, we identify a positive effect of election stakes on turnout.
Keywords: D72; H71; 330; voter motivation; elections; turnout; Wahlverhalten; Rationales Verhalten; Steuerpolitik; Wahl; Norwegen